2010
DOI: 10.1108/17508611011088823
|View full text |Cite
|
Sign up to set email alerts
|

Ethical climate in nonprofit and government sectors: the case of Japan

Abstract: Purpose -This is a study of ethical climates in nonprofit and government sectors in Japan, the aim of which is to determine the extent to which similarities (and differences) exist in ethical climate dimensions, what drives the differences and what are the implications for the sectors in this country. Design/methodology/approach -Using survey data and structural equation modeling techniques, the factors structure equivalence and measurement invariance of ethical climates in the two sectors were tested. The ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…Also, similarities in ethical standards govern ethical issues. In the same context a study in agreement with done by Laratta (2010) who found in Japan respondents showed similarity regarding ethical climate perception between government officials and executive of nonprofit directors. The previous result was contradicted with Ghorbani et al, (2014) who found that nurses at private hospital perceived ethical climate positively than public hospital nurses.…”
Section: Discussionsupporting
confidence: 82%
“…Also, similarities in ethical standards govern ethical issues. In the same context a study in agreement with done by Laratta (2010) who found in Japan respondents showed similarity regarding ethical climate perception between government officials and executive of nonprofit directors. The previous result was contradicted with Ghorbani et al, (2014) who found that nurses at private hospital perceived ethical climate positively than public hospital nurses.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas, data shows that PEC and BEC are the two ethical climates which are having a positive and significant relationship with OC and the finding is justified based on the understanding that these ethical climates have a significant and positive relationship with positive aspects of the job or organization. This relationship has been supported by different past studies (Laratta, 2010;Martin & Cullen, 2006;Oncer & Yildiz, 2012;Sial et al, 2019;Liu, 2020;Simha & Stachowicz-Stanusch, 2015;Tsai & Huang, 2008;Victor & Cullen, 1988) and is also supported by the study conducted by Mishra and Tikoria (2021), who studied that organizational climate has significant relationship with job commitment of the employees working in non-profit organizations.…”
Section: Discussionsupporting
confidence: 58%
“…The concept of ethical climate is powerful. According to Sims (1992), as quoted in Laratta (2008), an organization's ethical climate is a common set of identifications about what ethical behaviour is and how ethical challenges will be addressed. This atmosphere sets the tone for decision-making at all levels and under all conditions.…”
Section: Ethical Climatementioning
confidence: 99%